Evaluation of Clinical Characteristics and Laboratory Results of COVID-19 Iraqi Pregnant Women - Alaa Ibrahim Ali; Wassan Nori (AlQalam Journal of Medical and Applied Sciences, 2021)
Aims: To verify the value of simple blood indices as a predictor to COVID-19 infection among pregnant women. Methods: A prospective case-control study was carried in Al-Yarmouk Hospital from April 2020-till until April 2021 . A total of 80 pregnant women were recruited. Aged range 20-42 years, at 28-36+6 weeks of a singleton pregnancy. 40/80 tested +ve for COVID-19 based on real-time polymerase chain reaction test (PCR). Another 40/80 were taken as matched controls. Results: No statistically significant differences were reported upon comparing the two groups in terms of age and gestational age, (P-value= 0.341, 0.445, respectively). However, statistically difference were found for Hb, WBC, neutrophil count, lymphocyte count, platelet count, MPV, RCW, neutrophil/lymphocyte ratio, and platelets/lymphocyte ratio; all were significantly higher in the study group versus the healthy control with a P-value <0.0001. Conclusion: The neutrophil/lymphocyte ratio may serve as a critical factor determining the severity of COVID-19-infection in the early stages of the disease. Early detection and treatment of COVID-19 severe cases reduce the risk of an adverse pregnancy result.